2016
DOI: 10.1096/fj.201600213r
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of expression of venom toxins: silencing of prothrombin activator trocarin D by AG‐rich motifs

Abstract: Trocarin D (TroD), a venom prothrombin activator from Tropidechis carinatus, shares similar structure and function with blood coagulation factor Xa [Tropidechis carinatus FX (TrFX) a]. Their distinct physiologic roles are due to their distinct expression patterns. The genes of TroD and TrFX are highly similar, except for promoter and intron 1, indicating that TroD has probably evolved by duplication of FX, the plasma counterpart. The promoter insertion in TroD accounts for the elevated but not venom gland-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…A principle goal of many studies that discover and catalog silencers, is to gain insight into the mechanisms by which these noncoding sequence elements regulate transcription (Figure 3 Key Figure ). The discovery of silencers by studies focused on the genomic distribution of H3K27me3 [12] and PRC subunits that localize to H3K27me3 [20] clearly suggests the involvement of this pathway; furthermore, PRC2 previously has been implicated in silencer activity [44,65]. However, those studies which used a functional assay to define silencers did not observe a statistically significant enrichment of these chromatin marks on silencers [11,13], and only~10% of H3K27me3-DHSs were negatively correlated with nearby gene expression [12].…”
Section: Mechanisms Of Silencer Activitymentioning
confidence: 99%
“…A principle goal of many studies that discover and catalog silencers, is to gain insight into the mechanisms by which these noncoding sequence elements regulate transcription (Figure 3 Key Figure ). The discovery of silencers by studies focused on the genomic distribution of H3K27me3 [12] and PRC subunits that localize to H3K27me3 [20] clearly suggests the involvement of this pathway; furthermore, PRC2 previously has been implicated in silencer activity [44,65]. However, those studies which used a functional assay to define silencers did not observe a statistically significant enrichment of these chromatin marks on silencers [11,13], and only~10% of H3K27me3-DHSs were negatively correlated with nearby gene expression [12].…”
Section: Mechanisms Of Silencer Activitymentioning
confidence: 99%
“…In this study, emPAI scores of toxins in extruded venom were compared to transcript abundances in the venom gland and the venom sac, which revealed that both of these structures in the venom apparatus contribute to venom secretion. emPAI has also been used to investigate the contribution of promoter elements to expression of the prothrombin activating toxin TroD from venom of the rough-scaled snake Tropidechis carinatus [130] and to determine the relative abundance of toxin classes in venoms of the tarantula Phoneutria nigriventer [131] and the spine-bellied sea snake Hydrophis curtus, [132] If emPAI is used, it is necessary that a reasonable putative mature sequence is used for each precursor, to avoid bias due to signal peptides and pro-or post-peptides.…”
Section: Quantification Of Polypeptide Toxinsmentioning
confidence: 99%
“…More recently, it was found that AG-rich motifs, in the first intron, silence gene expression in non-venom gland tissues [71]. These AG-rich motifs are promotor-independent silencers, and such cis-elements are also found in some snake toxin genes, but not in housekeeping genes.…”
Section: Genome Data In the Reconstruction Of Toxin Evolutionmentioning
confidence: 99%